Evolution of facade design for commercial building in Kuala Lumpur (Jalan Tuanku Abdul Rahman and Jalan Ampang) / Raja Amirul Azman Raja Abdul Manan - Raja Abdul Manan, Raja Amirul Azman (2005)
The word ‘facade’ comes from the Latin fades, face, and has come to mean the main face or elevation of a building as seen from the street or other public place. The elements that are brought together can only be type and be divided into groups relating to wall surface, structure, fenestration and ornamentation. It is still the most essential architecture element and the most capable of communicating the function and significance of a building.